Implementasi Kebijakan Pemerintah Daerah Bali Dalam Pelestarian Ajaran Hindu Melalui Penyuluhan Keagamaan - I Wayan Suwadnyana; I Made Adi Widnyana; Ni Ketut Kantriani (Fakultas Hukum, Universitas Warmadewa, 2026)
This study examines the implementation of Bali’s local government policies in preserving Hindu teachings through religious counseling. The research method used is qualitative with a descriptive-analytical approach. The findings reveal that the local government has initiated various programs such as Dharma Wacana, Dharma Tula, short-term Pasraman, and religious competitions. However, the effectiveness of these efforts is constrained by limited human resources, financial support, and challenges posed by globalization. Recommendations highlight the importance of digitalizing religious counseling, improving the competence of counselors, and strengthening synergy between customary institutions and the local government to ensure the sustainability of Hindu teachings in Bali.